2013
DOI: 10.1093/icvts/ivt353
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative sildenafil therapy for pulmonary hypertension in infants undergoing congenital cardiac defect closure

Abstract: The low cost, the oral availability and the good tolerability of sildenafil make it a suitable and simple alternative therapy for secondary pulmonary hypertension including persistent postoperative pulmonary hypertension associated with ventricular septal defect in resource limited places. However, starting sildenafil early before surgery does not add a great benefit in terms of improving postoperative pulmonary hypertension or patients' outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 24 publications
7
35
0
2
Order By: Relevance
“…However, in the intensive care setting oral medications have the disadvantage of unpredictable absorption. Prophylactic use of sildenafil before surgical correction of CHD has been proven to be useful 30. The administration of intravenous sildenafil has been described31 32 but its effectiveness has not been clearly determined.…”
Section: Therapy Of Acute Ph In the Icumentioning
confidence: 99%
“…However, in the intensive care setting oral medications have the disadvantage of unpredictable absorption. Prophylactic use of sildenafil before surgical correction of CHD has been proven to be useful 30. The administration of intravenous sildenafil has been described31 32 but its effectiveness has not been clearly determined.…”
Section: Therapy Of Acute Ph In the Icumentioning
confidence: 99%
“…In the first study treatment with oral sildenafil two weeks prior to surgery was not superior to postoperative therapy in reducing mean pulmonary arterial pressure in a randomised controlled trial of VSD patients [17]. Nevertheless patients treated with sildenafil preoperatively had a shorter ICU stay.…”
Section: Discussionmentioning
confidence: 96%
“…Two of these reported that children who received sildenafil pre-and postoperatively had no crises or fewer crises than children who did not receive sildenafil (P = .02) 48 or who received sildenafil postoperatively only. 27 One trial reported that transient postoperative PH crises were more common in the sildenafil group than in the combination (sildenafil + milrinone) group (P = .02) and the milrinone-only group. 28 Three observational studies (1 prospective, 2 retrospective) in children with PH secondary to CHD included cases in which sildenafil was used to facilitate withdrawal of other pulmonary 26 Unaffected by sildenafi l: no sequelae and no hypotension with sildenafi l.…”
Section: Are Pde5 Inhibitors Effective In Improving Clinical Outcomesmentioning
confidence: 98%
“…El Midany et al (2013) 27 AE in both groups: pneumonia, need for reintubation, PH crises, renal failure requiring peritoneal dialysis. AE in sildenafi l pre-and postoperative group only: hematemesis.…”
Section: Are Pde5 Inhibitors Effective In Improving Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation